Comparing the Use of Books with Enhanced Records versus Those Without Enhancements: Methodology Leads to Questionable Conclusions - Haigh, Susan (Evidence Based Library and Information Practice, 2007)
A review of: Madarash-Hill, Cherie and J.B. Hill. “Electronically Enriched Enhancements in Catalog Records: A Use Study of Books Described on Records With URL Enhancements Versus Those Without.” Technical Services Quarterly 23.2 (2005): 19-31. Abstract Objective – To compare the use of books described by catalogue records that are enhanced with URL links to such information as dust jackets, tables of contents, sample text, and publishers’ descriptions, with the use of books described by records that are not enhanced with such links. Design – Use study. Setting – Academic library (Southeastern Louisiana University, Sims Memorial Library). Subjects – 180 records with enhancements and 180 records (different titles) without enhancements. Methods – The study identified the sample of unenhanced records by conducting searches of the broad subject terms “History”, “United States”, “Education”, and “Social” and limiting the searches to books. The enhanced sample was derived in the same manner, but with additional search limiters to identify only those records that had URL enhancements. An equal sample of enhanced and unenhanced records (50 or 30 of each) was tracked for each of four search terms. Only records for books that could be checked out were included, as use statistics were based on whether or not a book was borrowed. While half of the enhanced records had full-text elements (such as descriptions) that were indexed and thus searchable, the rate of use for these records was not tracked separately from the enhanced records that only had URL enhancements. Main results – Books described on records with URL enhancements for publisher descriptions, tables of contents, book reviews, or sample text had higher use than those without URL enhancements. Only 7% of titles with URLs, compared with 21% of those without, had not been borrowed. 74.67% of titles with URLs had been checked out one or two times, compared with 69.5% of those without URLs. The number of titles with enhanced records that had 3 or more checkouts was almost double the rate of unenhanced titles (18% to 9.5%). Conclusion – The authors conclude that catalogue records that have electronic links to book reviews, cover jackets, tables of contents, or publisher descriptions can lead to higher use of books, particularly if textual enhancements such as descriptions are also searchable.